Comments on reactions of oxide derivatives of uranium with hexachloropropene to give UCl4 - BAKER, ROBERT (My University, 2015)
We report that U3O8, UO2(NO3)2·6H2O, and UO2Cl2 react with hexachloropropene (HCP) to give UCl4 in 60, 100, and 92% yields, respectively, and report a protocol to recycle the HCP. This renders the preparation of UCl4 more accessible and sustainable. 2,5-Dichlorohexachlorofulvene has been identified as a significant by-product from these reactions
PUBLISHED
DOI: 10.1039/c5nj00476d